Feasibility of oncoplastic techniques in the surgical management of locally advanced breast cancer - Matthes, Angelo Gustavo Zucca [UNESP]; Uemura, Gilberto [UNESP]; Kerr, Ligia; Silva Matthes, Angelo Carmo; Michelli, Rodrigo Augusto D.; Azevedo Koike Folgueira, Maria Aparecida; da Costa Viera, Rene Aloisio (Elsevier B.V., 2012)
Background: Locally advanced breast cancer (LABC) is still common in developing countries. The association between neoadjuvant chemotherapy (NC) and oncoplastic surgery (OS) might provide an oncological treatment with satisfactory aesthetic results.Purpose: The goal was to demonstrate if oncoplastic surgical techniques can be utilized to treat LABC which was submitted to neoadjuvant chemotherapy.Methods: This prospective clinical trial included breast cancer patients, clinical stage III, who underwent established NC regimen. All patients underwent preoperative planning to control the tumor size and to define the surgical technique. A detailed analysis of the pathological specimen was performed.Results: 50 patients were assessed and surgically treated. Tumor size ranged from 3.0 to 14.0 cm (median 6.5 cm). Pathologic response was rated as stable, progressive, partial response, and complete response in 10%, 8%, 80% and 2% of the cases, respectively. Seventeen (34%) patients were submitted to OS. No patient had positive margins. Skin involvement was presented in 36% of pathologic specimen.Conclusions: Oncoplastic surgical techniques for selected patients decrease the rates of radical surgery despite large tumors. (www.clinicaltrials.gov, NCT00820690). (C) 2012 Surgical Associates Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: Breast cancer; Breast conserving treatment; Neoadjuvant therapy; Reconstructive surgical procedure; Pathology; Prospective study